The Analysis of Landslide Vulnerability Map and The Level of School Preparedness in Encountering Landslide in Gumelar Sub-District, Banyumas Regency. (April 2018) - Sani, A H M; Muryani, C; Rindarjono, M G
Abstract: Gumelar is one of sub-districts in Banyumas Regency where landslide frequently occurs. It is because most of areas in Gumelar have the slope from 15% until more than 40% and high rainfall, 1, 000-3, 000 mm/year. This research aimed to discover how high the level of vulnerability to landslides and the level of school preparedness in encountering the hazards in Gumelar sub-district. Areas vulnerable to landslides were determined by employing overlay method with rainfall, land slope, soil type, and land use as the parameters. While the sample of schools was obtained by employing purposive random sampling, selecting a junior high school located in landslide prone areas. Data of school preparedness was obtained through interview and questionnaire. The research results revealed that there were three categories of landslide vulnerability; high (6572.06 ha), moderate (2653.05 ha) and low (93.79 ha). Villages that had high vulnerability were Samudra Kulon, Tlaga, Cilangkap, Paningkaban, and Karangkemojing; while the level of school preparedness in encountering landslide was categorized as unready.